2021
DOI: 10.1002/advs.202004640
|View full text |Cite
|
Sign up to set email alerts
|

Defect Induced Polarization Loss in Multi‐Shelled Spinel Hollow Spheres for Electromagnetic Wave Absorption Application

Abstract: Defect engineering is an effective approach to manipulate electromagnetic (EM) parameters and enhance absorption ability, but defect induced dielectric loss dominant mechanism has not been completely clarified. Here the defect induced dielectric loss dominant mechanism in virtue of multi-shelled spinel hollow sphere for the first time is demonstrated. The unique but identical morphology design as well as suitable composition modulation for serial spinels can exclude the disturbance of EM wave dissipation from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
107
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 266 publications
(107 citation statements)
references
References 68 publications
0
107
0
Order By: Relevance
“…The differences in work function of materials are reported to cause the redistribution and accumulation of charges in interfaces thus leading to interfacial polarization. [26,[66][67][68][69] The work function of Ni, ZnO, NiO, and NiFe 2 O 4 are 5.1, 5.3, 5.4, and 4.61 eV, respectively. [70][71][72][73] In Zn5, the interfacial polarization comes from Ni/ZnO (5.1 eV/5.3 eV) interface.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in work function of materials are reported to cause the redistribution and accumulation of charges in interfaces thus leading to interfacial polarization. [26,[66][67][68][69] The work function of Ni, ZnO, NiO, and NiFe 2 O 4 are 5.1, 5.3, 5.4, and 4.61 eV, respectively. [70][71][72][73] In Zn5, the interfacial polarization comes from Ni/ZnO (5.1 eV/5.3 eV) interface.…”
Section: Resultsmentioning
confidence: 99%
“…Hard ferrites, which are difficult to magnetize due to their high coercivity, are used to produce permanent magnets that have been used for applications in the loudspeaker, refrigerator, communication system, washing machine, TV, switchmode power supply, dc-dc converter, microwave absorption system, etc. [4,[7][8][9]. On the other side, soft ferrites behave as good conductors at low magnetic field due to their low coercivity, whose magnetization can be easily altered.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that CuCo 2 S 4 nanoparticles and FCMT/CuCo 2 S 4 nanocomposite showed the considerable imaginary part of permeability, derived from the intrinsic features of nanoparticles. These phenomena are realized by the produced crystal defects, distortions, and dislocations, as well as the induced magnetic dipole moments, established by the unique interactions at grain boundaries 104 , 105 . Eddy current loss plays a vital role in microwave absorption.…”
Section: Resultsmentioning
confidence: 99%